Maternal and umbilical cord copeptin levels in pregnancies complicated by fetal growth restriction - Bulbul, Gul Alkan; Kumru, Selahattin; Erol, Onur; Isenlik, Bekir Sitki; Ozdemir, Ozgur; Caglar, Mete; Aydin, Suleyman (Taylor & Francis Ltd, 2015)
Objective: The aim of this study was to compare maternal and fetal serum copeptin concentrations in pregnancies complicated by isolated fetal growth restriction (FGR), and uncomplicated pregnancies, and to investigate relationships between copeptin levels and clinical parameters. Methods: Maternal and fetal serum copeptin levels were measured in 21 women with pregnancies complicated by isolated FGR and 20 women with normal pregnancies (control group). Doppler assessment of the uterine and umbilical arteries was performed in each patient. Results: Maternal serum copeptin levels were significantly higher in women with isolated FGR compared to controls (p = 0.042). In addition, maternal copeptin levels were inversely correlated with the uterine artery pulsatility and resistance indices and positively correlated with neonatal birth weight. Umbilical vein copeptin levels were significantly increased in neonates with adverse outcomes (p = 0.001). Conclusions: Increased maternal copeptin concentration may reflect a response to stress, thus serving as a compensatory mechanism in pregnancies complicated by FGR.
Keywords: Copeptin; Doppler velocimetry; fetal growth restriction; neonatal outcome; pregnancy